Diagnostic performance of ankle ultrasound for diagnosing anterior talofibular and calcaneofibular ligament injuries: a meta-analysis. (May 2020) - Seok, Hosik; Lee, Sun Hwa; Yun, Seong Jong
Background: Ankle ultrasound imaging could be an option with higher priority due to its lack of radiation, and cost- and time-effectiveness. However, previous studies regarding anterior tibiofibular ligament and calcaneofibular ligament injuries have shown varied results. Purpose: To evaluate the diagnostic performance of ankle ultrasound for anterior tibiofibular ligament and calcaneofibular ligament injuries. Material and Methods: PubMed and EMBASE databases were searched for diagnostic accuracy studies that used ultrasound for diagnosing anterior tibiofibular ligament and calcaneofibular ligament injuries. Bivariate and hierarchical summary receiver operating characteristic modeling were used to evaluate diagnostic performance. Subgroup analysis was performed using studies according to severity of the injury (complete and partial anterior tibiofibular ligament tear). We performed meta-regression analyses for heterogeneity exploration. Results: Ten articles involving a total of 380 patients were included. For anterior tibiofibular ligament injury, the summary sensitivity, summary specificity, and area under the hierarchical summary receiver operating characteristic curve (AUC) were 0.99, 0.92, and 0.99, respectively. For calcaneofibular ligament injury, the summary sensitivity, summary specificity, and AUC were 0.95, 0.99, and 0.95, respectively. In subgroup analysis, for complete anterior tibiofibular ligament tear, the summary sensitivity, summary specificity, and AUC were 0.96, 0.82, and 0.96, respectively. For partial anterior tibiofibular ligament tear, the summary sensitivity, summary specificity, and AUC were 0.90, 0.82, and 0.93, respectively. Among the various potential covariates, proportion of anterior tibiofibular ligament tear, ultrasound interpreter, and reference standard were associated with specificity heterogeneity. Conclusion: Ankle ultrasound demonstrates high diagnostic performance in the diagnosis of anterior tibiofibular ligament and calcaneofibular ligament injuries. We recommend ultrasound performed by a musculoskeletal radiologist as a first-line diagnostic tool to diagnose anterior tibiofibular ligament and calcaneofibular ligament injuries.